Negociação coletiva em tempos de crise: a polêmica quanto à prevalência do negociado sobre o legislado no sistema sindical brasileiro - Meirelles, Davi Furtado (2018)
The controversial debate on the prevalence of “negotiated over legislated” has stimulated several studies about the real extent of private collective autonomy in labor relations. Can freedom to negotiate - and thus to seek a regulation closer to reality for the parties directly concerned, especially in times of economic crisis - allow the disregard of legally and long regulated rights? Would the flexibilization of these rights necessarily require deregulation of those same rights? If there are compensatory clauses, is it possible and valid the negotiation that chooses not to apply rights enshrined in labor legislation, without compromising the principle of worker protection? The analysis of these issues is at stake when trying to achieve the best possible balance in collective labor relations